Integrative Proteomic and Phosphoproteomic Analyses of Pattern- and Effector-Triggered Immunity in Tomato - Yu, Juanjuan; Gonzalez, Juan M.; Dong, Zhiping; Shan, Qianru; Tan, Bowen; Koh, Jin; Zhang, Tong; Zhu, Ning; Dufresne, Craig; Martin, Gregory B.; Chen, Sixue (Frontiers in Plant Science, 2021)
Plants have evolved a two-layered immune system consisting of pattern-triggered immunity (PTI) and effector-triggered immunity (ETI). PTI and ETI are functionally linked, but also have distinct characteristics. Unraveling how these immune systems coordinate plant responses against pathogens is crucial for understanding the regulatory mechanisms underlying plant defense. Here we report integrative proteomic and phosphoproteomic analyses of the tomato-Pseudomonas syringae (Pst) pathosystem with different Pst mutants that allow the dissection of PTI and ETI. A total of 225 proteins and 79 phosphopeptides differentially accumulated in tomato leaves during Pst infection. The abundances of many proteins and phosphoproteins changed during PTI or ETI, and some responses were triggered by both PTI and ETI. For most proteins, the ETI response was more robust than the PTI response. The patterns of protein abundance and phosphorylation changes revealed key regulators involved in Ca2+ signaling, mitogen-activated protein kinase cascades, reversible protein phosphorylation, reactive oxygen species (ROS) and redox homeostasis, transcription and protein turnover, transport and trafficking, cell wall remodeling, hormone biosynthesis and signaling, suggesting their common or specific roles in PTI and/or ETI. A NAC (NAM, ATAF and CUC family) domain protein and lipid particle serine esterase, two PTI-specific genes identified from previous transcriptomic work, were not detected as differentially regulated at the protein level and were not induced by PTI. Based on integrative transcriptomics and proteomics data, several potential PTI and ETI-specific markers are proposed. These results provide insights into the regulatory mechanisms underlying PTI and ETI in the tomato-Pst pathosystem, and will promote future validation and application of the disease biomarkers in plant defense.